2022
DOI: 10.1038/s41467-022-28607-y
|View full text |Cite
|
Sign up to set email alerts
|

Reversible dehydrogenation and rehydrogenation of cyclohexane and methylcyclohexane by single-site platinum catalyst

Abstract: Developing highly efficient and reversible hydrogenation-dehydrogenation catalysts shows great promise for hydrogen storage technologies with highly desirable economic and ecological benefits. Herein, we show that reaction sites consisting of single Pt atoms and neighboring oxygen vacancies (VO) can be prepared on CeO2 (Pt1/CeO2) with unique catalytic properties for the reversible dehydrogenation and rehydrogenation of large molecules such as cyclohexane and methylcyclohexane. Specifically, we find that the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 61 publications
1
46
0
Order By: Relevance
“…Previous attempts showed that by decreasing the size of metal to atomic scale, the resulting cationic metal single atoms with less d-electrons tend to bind CO in a less intensive manner 12 15 . As for the hydrogenation of aromatic substrate which generally requires metal ensemble sites 16 20 , Su et al recently discovered that with the assistance of neighboring oxygen vacancies, Pt single atom catalyst manifests even higher toluene hydrogenation performance than catalysts with Pt nanoparticles (NPs) 21 . Despite the theoretical potential of single atom catalysts in driving the CO-tolerant toluene hydrogenation process, their attenuated interaction toward CO would inevitably compromise the purification capabilities toward the crude hydrogen feed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts showed that by decreasing the size of metal to atomic scale, the resulting cationic metal single atoms with less d-electrons tend to bind CO in a less intensive manner 12 15 . As for the hydrogenation of aromatic substrate which generally requires metal ensemble sites 16 20 , Su et al recently discovered that with the assistance of neighboring oxygen vacancies, Pt single atom catalyst manifests even higher toluene hydrogenation performance than catalysts with Pt nanoparticles (NPs) 21 . Despite the theoretical potential of single atom catalysts in driving the CO-tolerant toluene hydrogenation process, their attenuated interaction toward CO would inevitably compromise the purification capabilities toward the crude hydrogen feed.…”
Section: Introductionmentioning
confidence: 99%
“…Dehydrogenation of MCH and heterocyclic compounds was conducted in a fixed‐bed flow type reactor in recently reported articles [3d,e,h] . In these reports, mixture of substrate and inert gas (Ar or N 2 ) was streamed generally, because dilution of generated hydrogen by inert gas could shift the equilibrium toward dehydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…213 Recently, Prendergast, Somorjai, and Su reported a SAC based on Pt 1 / CeO 2 which greatly enhanced the reaction rate of cyclohexane dehydrogenation. 214 More specifically, the activity of this catalyst system was 300-fold higher than that of conventional NPs catalysts (Pt/CeO 2 and Pt/Al 2 O 3 ). Moreover, this SAC was applicable in the MCH/toluene system.…”
Section: ■ Aromatic Hydrocarbonsmentioning
confidence: 86%
“…To achieve activity, the catalyst precursor (PdO/CeO 2 ) must be pretreated at reducing conditions (H 2 , 200 °C, 1 h) . Recently, Prendergast, Somorjai, and Su reported a SAC based on Pt 1 /CeO 2 which greatly enhanced the reaction rate of cyclohexane dehydrogenation . More specifically, the activity of this catalyst system was 300-fold higher than that of conventional NPs catalysts (Pt/CeO 2 and Pt/Al 2 O 3 ).…”
Section: Aromatic Hydrocarbonsmentioning
confidence: 99%